Air Pollution: Sources and Global Statistics - Zorzos, Achilleas; Alexiadis, Antonis; Zacharopoulos, Stavros (Open Schools Journal for Open Science, 2019)
Air pollution is called the presence of any kind or form of substances, noise or radiation found in the atmosphere in such a quantity, concentration or duration capable of causing harm in human health, living organisms and ecosystems. By understanding the reasons behind the increase of air polluting substances in the atmosphere, we may have better chances of solving the problem in the future.